Assessment of Right Ventricle Function in Patients with Mitral Repair: Case Series - Yannis Amador; Jacobo Moreno Garijo; Azad Mashari; Giovanni Gadotti; Wilma M. Hopman; Tirone E David; Massimiliano Meineri (Annals of Cardiac Anaesthesia)
Objectives: We aim to assess right ventricular function in patients undergoing mitral valve repair using trans-esophageal echocardiography, focusing on the predictive value of right ventricular longitudinal strain compared to other echocardiographic measures. Design: Retrospective analysis. Setting: Toronto General Hospital. Participants: Thirty elective patients undergoing mitral valve repair. Interventions: Quantitative assessment of right ventricular function using transesophageal echocardiography images pre- and post-mitral valve repair, including right ventricular longitudinal strain, fractional area change, tricuspid annular plane systolic excursion, and systolic peak velocity (S’). Measurements and Main Results: 3 patterns of RV strain were identified with right ventricular longitudinal strain emerging as the most significant discriminator among right ventricular functional subgroups, with 43% of cases showing worsening, 20% showing no change, and 37% showing improvement. No correlation was found between right ventricular performance parameters and the need for vasopressors post-cardiopulmonary bypass. There was also no association between initial right ventricular longitudinal strain and difficulty in weaning off bypass or increased demand for pressors. Changes in tricuspid annular plane systolic excursion across all cases warrant further investigation with a larger cohort. Conclusions: Right ventricular longitudinal strain is a valuable tool for assessing right ventricular function post-mitral valve repair, offering insights into immediate postoperative outcomes and long-term right ventricular remodeling. Despite limitations like single-surgeon experience and institution-specific choice of pressors, our study provides useful insights into right ventricular function post-mitral repair surgery, paving the way for future research in larger patient populations.